SUSTAINABLE PUBLIC POLICY IN THE FACE OF CLIMATE CHANGE: A COMPARATIVE STUDY OF GLOBAL BEST PRACTICES - Amas Mashudin (Penelitian dan Pengembangan Ilmu, 2024)
Climate change is an urgent global challenge, requiring a systematic and sustainable public policy response. This research aims to identify the main principles and characteristics of sustainable public policies that are effective in mitigating and adapting to climate change in various countries. Using a Systematic Literature Review (SLR) approach, we analyze 40 peer-reviewed articles published in the last decade. Findings show that successful policies are based on principles such as good governance, evidence-based approaches, and cross-sector collaboration. Additionally, characteristics of effective policies include a strong regulatory framework, market-based instruments, and transparent monitoring mechanisms. A comparative analysis of best practices, including the European Green Deal, US Inflation Reduction Act, Nordic Climate Governance Model, And Indonesia’s Low Carbon Development Initiative, reveals that a combination of regulatory strategies and economic incentives can significantly reduce greenhouse gas emissions. This research provides valuable insights for policymakers in designing more adaptive and effective climate policies.